Court Delay and Law Enforcement in China Civil process and economic perspective - Jiang, Qing-Yun (Ökonomische Analyse des Rechts, 2006)
Many countries, especially developing countries, have experienced how difficult it is to make their judiciary systems function. Court delays, backlogs and uncertainty associated with unexpected court outcomes affect the quality of justice. On the basis of an empirical study and taking a comparative as well as an economic perspective Qing-Yun Jiang analyses the problem of court delay and law enforcement in China. He shows that delay is not a serious problem in the lower courts in respect to trial cases, but mainly in appeal cases and retrial cases, which require more time. Moreover, the study confirms that law enforcement has been an obstacle for the development of market economy and a bottleneck of the judiciary. The author concludes that judicial reform should not only deal with symptoms, but with the roots of the political and economic structure.